Law Enforcement against Pedicap which is Modified into "Bentor" - Ryke Rhimadhila; Bambang Tri Bawono (Law Development Journal, 2020)
The aim of this study To find out and analyze the causes of the many pedicabs being modified into motorized pedicabs in the jurisdiction of the Semarang Police, law enforcement of Act No. 22 of 2009 concerning Road Traffic and Transportation against bumps in the jurisdiction of the Semarang Police, obstacles and solutions in overcoming pedicab law enforcement modified in the jurisdiction of the Semarang Police. The approach method used is juridical normative and juridical sosilogis, the specifications in this research are descriptive analysis, population and sampling methods, data collection techniques using literature study and interviews, data analysis used is qualitative. The research problem is analyzed by law enforcement theory and law effectiveness theory. The number of Bentors as urban transportation shows an increase, this is due to the increasing need for transportation facilities and also transportation service areas that cannot be served by other transportation facilities, because of the difficulty of finding work, many unemployment. Law enforcement against Bentor violations in the jurisdiction of the Unit Polrestabes Semarang refers to Article: 277 of Act No. 22 of 2009. Law enforcement of Act No. 22 of 2009 concerning Highway Traffic and Transportation regarding the prohibition of driving motorized pedicabs has several obstacles, namely the law enforcement factor. The second is the factor of facilities or facilities, namely in the case of confiscation of vehicles where the Police cannot secure large numbers of bumps because the facilities used to transport the bumps are insufficient, the number of Bentors in Semarang. The last factor is the low level of public awareness of the enactment of Act No. 22 of 2009, besides that the community also does not understand the consequences that will be received if they still use Bentor. The solution in overcoming obstacles is by coordinating the Semarang Police with the Semarang City Transportation Agency in enforcing the motorized pedicab law in the city of Semarang as follows: Unity of action, communication, division of labor and strengthening through law.